Origin and functional role of antisense transcription in endogenous and exogenous retroviruses - Fabio Romerio (Retrovirology, 2023)
Abstract Most proteins expressed by endogenous and exogenous retroviruses are encoded in the sense (positive) strand of the genome and are under the control of regulatory elements within the 5’ long terminal repeat (LTR). A number of retroviral genomes also encode genes in the antisense (negative) strand and their expression is under the control of negative sense promoters within the 3’ LTR. In the case of the Human T-cell Lymphotropic Virus 1 (HTLV-1), the antisense protein HBZ has been shown to play a critical role in the virus lifecycle and in the pathogenic process, while the function of the Human Immunodeficiency Virus 1 (HIV-1) antisense protein ASP remains unknown. However, the expression of 3’ LTR-driven antisense transcripts is not always demonstrably associated with the presence of an antisense open reading frame encoding a viral protein. Moreover, even in the case of retroviruses that do express an antisense protein, such as HTLV-1 and the pandemic strains of HIV-1, the 3’ LTR-driven antisense transcript shows both protein-coding and noncoding activities. Indeed, the ability to express antisense transcripts appears to be phylogenetically more widespread among endogenous and exogenous retroviruses than the presence of a functional antisense open reading frame within these transcripts. This suggests that retroviral antisense transcripts may have originated as noncoding molecules with regulatory activity that in some cases later acquired protein-coding function. Here, we will review examples of endogenous and exogenous retroviral antisense transcripts, and the ways through which they benefit viral persistence in the host.